Friction Stir Spot Welding of Aluminium Alloy AA5052 With and Without Carbon Fiber-reinforced Polymer Composite Interlayer - Kalaf, Omer (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In this dissertation, similar aluminum alloys AA5052 with additional carbon fiber reinforced polymer composite (CFRP) interlayer were selected to investigate the effect of welding parameters (rotational speed and dwell time) on the mechanical properties, joint efficiency, and microstructure of friction stir spot weld joint. The maximum tensile shear load was 1779.6 N with joint efficiency of 14.6% obtained at rotational speed of 2,000 rpm and 2 s dwell time, which is 39.5% higher than the value at low rotational speed 850 rpm and 2 s dwell time whereas the joints without interlayer the maximum tensile shear load was 2439 N with joint efficiency of 19.4% obtained at 1300 rpm and 2 s dwell time, which is 48% higher than the value at low rotational speed 850 rpm and 5 s dwell time. Meanwhile, the maximum microhardness 58 HV was attained in the keyhole region at rotational speed of 2,000 rpm and dwell time of 5 s, which is 22.4% higher compared to low rotational speed. On the other hand the specimens without carbon fiber interlayer, the maximum microhardness was 37.2 HV was obtained at 850 rpm and 2 second dwell time in thermal mechanical affect zone, which is about 51% higher compared to low rotational speed. The SEM-EDS results reveal the presence of intermetallic compounds (Al–Mg–C), which enhance the intermetallic bonding between elements. The microstructure without interlayer images showed that welding parameters such as rotational speed and dwell time have high effect on hook deformation and penetration around the pin area. It was proposed a novel prediction model to predict tensile shear load of samples with and with CFRP interlayer by applying various machine learning models i.e. artificial neural network (ANN), Adopted neuro fuzzy-inference system (ANFIS), support vector machine (SVM) and multi linear regression (MLR). According to test results, it has an incentive effect for future studies to know that MLR model produce better results to estimate tensile shear load in both cases of with and without additional interlayer rather than the other model and the average error was just 0.333% and 3.64 % respectively.

ÖZ: Bu savunma tezinde, kaynak parametrelerinin (dönme hızı ve bekleme süresi) mekanik özellikler, bağlantı verimliliği ve sürtünme karıştırma noktasının mikro yapısı üzerindeki etkisini araştırmak için ek karbon fiber takviyeli polimer kompozit (CFRP) ara tabakalı benzer alüminyum alaşımları AA5052 seçilmiştir. kaynak bağlantısı. Maksimum çekme kesme yükü 1779,6 N olup, 2.000 rpm dönme hızı ve 2 sn bekleme süresinde elde edilen % 14,6 eklem verimliliği ile, düşük dönme hızı 850 rpm ve 2 sn bekleme süresindeki değerden% 39,5 daha yüksektir, oysa eklemsiz eklemler ara tabaka maksimum gerilme kesme yükü 2439 N idi ve 1300 rpm'de ve 2 sn bekleme süresinde elde edilen% 19,4'lük eklem verimliliği, 850 rpm düşük dönme hızı ve 5 sn bekleme süresindeki değerden% 48 daha yüksektir. Bununla birlikte, anahtar deliği bölgesinde 2.000 rpm dönme hızında ve 5 saniyelik bekleme süresinde maksimum mikro sertlik 58 HV elde edildi, bu da düşük dönme hızına göre% 22.4 daha yüksek. Öte yandan karbon fiber ara tabakası olmayan numunelerde maksimum mikro sertlik 850 rpm'de 37,2 HV ve düşük dönme hızına göre yaklaşık% 51 daha yüksek olan termal mekanik etki bölgesinde 2 saniye bekleme süresinde elde edilmiştir. SEM-EDS sonuçları, elementler arasındaki intermetalik bağı güçlendiren intermetalik bileşiklerin (Al – Mg – C) varlığını ortaya koymaktadır. Katmanlar arası görüntülerin olmadığı mikro yapı, dönme hızı ve bekleme süresi gibi kaynak parametrelerinin kanca deformasyonu ve pim alanı etrafındaki penetrasyon üzerinde yüksek etkiye sahip olduğunu göstermiştir. Yapay sinir ağı (YSA), Kabul edilen nöro bulanık çıkarım sistemi (ANFIS), destek vektör makinesi (SVM) ve çoklu doğrusal regresyon (MLR). Test sonuçlarına göre, MLR modelinin her iki durumda da diğer modelden ziyade ilave ara katmanı olan ve olmayan çekme kesme yükünü tahmin etmede daha iyi sonuçlar ürettiğini ve ortalama hata sadece sırasıyla % 0,333 ve 3,64 olduğunu bilmek gelecekteki çalışmalar için teşvik edici bir etkiye sahiptir.
Doctor of Philosophy in Mechanical Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2021. Co-Supervisor: Asst. Prof. Dr. Mohammed Asmael and Supervisor: Asst. Prof. Dr. Babak Safaei
Keywords: Mechanical Engineering; Material--Materials Engineering; Viscoelastic materials; friction stir spot welding; interlayer; carbon fiber-reinforced polymer composite; aluminum alloys; mechanical properties; microstructure; machine learning